2005
DOI: 10.1021/ma052055x
|View full text |Cite
|
Sign up to set email alerts
|

Subphase pH Effect on Surface Micelle of Polystyrene-b-poly(2-vinylpyridine) Diblock Copolymers at the Air−Water Interface

Abstract: The subphase pH effect on the surface micelles of polystyrene-b-poly(2-vinylpyridine) (PS-b-P2VP) diblock copolymers was investigated by the π−A isotherm and the morphology of the Langmuir−Blodgett (LB) film. Ionization of P2VP block significantly affects the π−A isotherm of the surface micelles at the air−water interface. At high pH, where the degree of ionization is low, the π−A isotherm shows a more expanded form and high transition surface pressure reflecting the strong tendency of P2VP blocks spreading on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 31 publications
4
101
1
Order By: Relevance
“…The variation of morphology of 18-Ar-18,2Br −1 with increasing surface pressure at the air/water interface resembles that of the diblock copolymers [51][52][53]. Prior to A L being reached, a complete absence of surface pressure suggests that the alkyl chains are in horizontal configuration.…”
Section: Morphologies Of Langmuir-blodgett Monolayersmentioning
confidence: 85%
“…The variation of morphology of 18-Ar-18,2Br −1 with increasing surface pressure at the air/water interface resembles that of the diblock copolymers [51][52][53]. Prior to A L being reached, a complete absence of surface pressure suggests that the alkyl chains are in horizontal configuration.…”
Section: Morphologies Of Langmuir-blodgett Monolayersmentioning
confidence: 85%
“…In fact, the size of features in the SFM images matches exactly with the calculated area/molecule deposited with the LB trough further supporting an average molecular weight of the comb molecules as being around 130 kDa. Some research into creating dense layers via amphiphilic copolymer LB assembly has been performed in the past [26][27][28][29][30][31][32][33][34][35], but we have shown that multi-molecular micellation (creating structures > 100 nm) has been largely prevented through controlling polymer chain architecture. Such films could potentially be used as ultrathin size-selective nanofiltration films for sensor applications, templates for nanolithography, or an environmentally acceptable way to tune the physical and chemical properties of a flat surface.…”
Section: Preparation Of Langmuir-blodgett (Lb) and Langmuir-schäfer (mentioning
confidence: 96%
“…The q y of these peaks relates to the long period, the average distance between stacked crystalline lamellae. The Yoneda peak arises in the in-plane direction owing to the interference effect of the incident and scattered wave (Chung et al, 2006). By stepwise annealing, these scattering peaks slightly shifted to the lower q y range in the in-plane direction and increased in relative intensity with an increase in T a .…”
Section: Figurementioning
confidence: 98%
“…GISAXS analysis based on distorted-wave Born approximation (DWBA) theory was applied for various multi-layer systems consisting of these films and substrates (Mü ller-Buschbaum et al, 2004;Xu et al, 2004;Tang et al, 2005;Park et al, 2005;Chung et al, 2006). In this study, we have tried to detect grazingincidence small-angle and wide-angle X-ray scattering (GISWAXS) from crystalline polymer thin films.…”
Section: Introductionmentioning
confidence: 99%